Production and characterization of Al-xNi in situ composites using hot pressing - Yamanoglu R. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this study, a new metal matrix composite of aluminium was designed with the addition of nickel alloy particles. To produce in situ intermetallic formation, aluminium-nickel powder mixtures with different ratios ranging from 5 to 40 wt% Ni were consolidated at 550ºC for 15 minutes under 40 MPa pressure. The interlayer phase formed during sintering was determined using X-ray diffraction and energy dispersive X-ray spectroscopy. The effect of nickel and Al-Ni intermetallics on the mechanical properties of the material was studied. The results demonstrated that the addition of nickel enhanced the hardness and wear behaviour of aluminium by forming a strong bonding interface between the aluminium and nickel particles.